Identifying Caregiver Needs for Children With a Tracheostomy Living at Home. (November 2020) - Mai, Katherine; Davis, Renee K.; Hamilton, Sue; Robertson-James, Candace; Calaman, Sharon; Turchi, Renee M.
This study sought to understand caregiver needs of children with tracheostomies (CWT) living at home and inform development of standardized tracheostomy simulation training curricula. Long-term goals are decreasing hospital readmissions following tracheostomy placement and improving family experiences while implementing a medical home model. We recruited caregivers of CWT and conducted semistructured interviews, subsequently recorded, transcribed, and analyzed for emerging themes using NVivo. Demographic data were collected via quantitative surveys. Twenty-seven caregivers participated. Emerging themes included the following: (1) caregivers felt overwhelmed, sad, frightened when learning need for tracheostomy; (2) training described as adequate, but individualized training desired; (3) families felt prepared to go home, but transition was difficult; (4) home nursing care fraught with difficulty and yet essential for families of CWT. Families of CWT have specific needs related to discharge training, resources, support, and home nursing. Provider understanding of caregiver needs is essential for child well-being, patient-/family-centered care, and may improve health outcomes.